MODERNISASI PERTANIAN TERHADAP PEMAKAIAN PUPUK DALAM MENINGKATKAN TARAF HIDUP PETANI DI DESA SIRISIRISI KECAMATAN DOLOKSANGGUL SUMATERA UTARA - Togatorop, Anita; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Modernization can be used in the field of agriculture in Indonesia is marked with a fundamental change in the patterns of agriculture, from traditional ways to be in ways that are more modren. One of the types of changes that occurred in the village of Sirisirisi namely the changes in the use of organic fertilizer (natural fertilizer) become inorganic fertilizer (chemical fertilizers). This research aims to analyze how the modernization of the use of inorganic fertilizer affect social change the culture of the society tani. The impact of modernisation of social change the culture of the society tani is increasing agricultural productivity in Indonesia. The method used in this research is a descriptive quantitative method .The results of this research showed that the factors encouraging the public to accept the changes to the formal education system that developed, open system (open society stratification), the orientation to the future and the PPL (Agricultural Extension field). There are some of the impacts of modernization the use of inorganic fertilizer is the positive impact of the farmers planting pattern and increase the productivity of agricultural products and improve the living standard of farmers and the negative impacts of the use of inorganic fertilizer is the use of fertilizers affect the addition of the cost of treatment plant crops and the environment is changed. The success of the agricultural system can be seen to give better living conditions of the farmers in the village sirisirisi. Now the suggestions proposed by the author of the farmers to the use of inorganic fertilizer does not use excessive dose is due to the level of the fertility of the land will be reduced due to the lack of hara element in the land.Key Words : the impact of the use of fertilizer, living standard of farmers